ANTIULCEROGENIC BENEFITS OF HERBAL INGREDIENTS IN ETHANOL-INDUCED ANIMAL MODELS - Bi, Weiping; Man, Huibin; Hu, Lizhi; Man, Mao-Qiang (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
pathogenesis of gastric ulcer. Although therapeutic approaches are widely available, preventive regimens are limited. Numerous studieshave demonstrated that herbal medicines display preventive benefit in the development of ethanol-induced gastric ulcers in both rat andmouse models. The preventive efficacy of herbal medicines on the development of ethanol-induced gastric ulcers is comparable orsuperior to histamine receptor 2 antagonists. But herbal medicines have fewer side effects.Materials and Methods: Keywords including gastric ulcer, herbal medicines, prevention and natural ingredients were used to searchon http://www.ncbi.nlm.nih.gov/pubmed. The search was performed on January 12, 2014. Only articles published in English were usedin this review.Result and Conclusion: According to the mechanisms of their action and pathogenesis of gastric ulcer, combination of certain herbalmedicines could be a valuable alternative to prevent the development of gastric ulcer, particularly for the subjects who are at a higher riskof developing gastric ulcer.